PERBANDINGAN DAYA HAMBAT ANTARA DUA JENIS PROBIOTIK YANG BERBEDA TERHADAP BAKTERI Aggregatibacter actinomycetemcomitans - Hesty Pradini; Sutji Asri Tjitra A; Rochman Mujayanto; Arlina Nurhapsari (Jurnal Medali, 2013)
Probiotics is live microorganisms which is given in adequate amounts in the form of food Probiotics is live microorganisms which are given in adequate amounts in the form of food or supplements provide health benefits to the body. Probiotics Bacteria has to unleash antimicrobial substances such as organic acids, hydrogen peroxide and bacteriocins. The aim of the study is to know inhibition differences between two different types of probiotic bacteria toward Aggregatibacter actinomycetemcomitans.The study was conducted by using two different types of probiotics, the probiotics containing bacteria Lactobacillus acidophilus and Bifidobacterium and probiotic containing bacteria Lactobacillus bulgaricus and Streptococcus thermophiles, and sterile distilled water as a negative control group. The antibacterial properties of the extracts were tested using by chamber diffusion method and incubated Â± 24hours, then by measuring inhibition zone (light zone) around the chamber using calipers.The average resistance zone of probiotics which contains probiotic bacteria Lactobacillus acidophilus and Bifidobacterium, probiotic bacteria Lactobacillus bulgaricus and Streptococcus thermophiles successive sequence were 3.13 mm, and 1.87 mm. There were differences with One Way Anova in the groups treated with significance of 0.000.From the results, it concluded that there were differences in the inhibition of the two types of probiotic bacteria on the growth of Aggregatibacter actinomycetemcomitans.Â Keywords : Probiotics, Lactobacillus acidophilus and Bifidobacterium, Lactobacillus bulgaricus and Streptococcus thermophiles, resistibility, Aggregatibacter actinomycetemcomitans